Problematizing the Contested Notion of Nation in Afghanistan: A Reflection on the Afghan Conundrum in Nadeem Aslam’s The Wasted Vigil - DAS, AVIJIT; Rai, Shri Krishan (SARE: Southeast Asian Review of English, 2023)
Abstract: The portrayal of nationalism in the context of establishing reconciliation, justice, and peace in the conflicting zone of Afghanistan has been stereotypical in mainstream literature, often referring to radical religious beliefs as the source of violence and inherent instability in the region. Of late, critics have been resounding the problematics of conflicts in various dimensions, like economic, cultural, social, religious, and so on, to focus upon the probabilities of reconciliation, justice, and peace, which are the basics of a desirable human civilization. While nuclear weapons and postmodern dissatisfaction are leading the entire civilization onto the brink of complete annihilation, the worst crimes are being witnessed in many disputed territories, making these regions’ geopolitical standings prone to renewed discovery. The literature of recent times, dialoguing their discourses, opens up fascinating facades to explore. The present study intends to show how Nadeem Aslam’s The Wasted Vigil provides a critical understanding of the contested notion of Afghan nationalism in its multidimensional fledglings. Keywords: Afghan nationalism, Conflicting zones, Reconciliation, Stereotyping, Peace.